The Developing Simple Composition Writing Skills Through Interactive Picture Media in Elementary School Students - Nurman Alamsyah; Briliani Fitri Fadhillah (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2026)
Writing is one of the most fundamental language skills in elementary education, yet it remains a persistent challenge due to passive and teacher-centered instructional approaches. This study aims to improve the simple essay writing skills of third-grade students at SDN 01 Pasirmuncang, Caringin District, Bogor Regency, through the implementation of interactive picture media. In the pre-cycle phase, only 11 out of 36 students (30.56%) met the Minimum Mastery Criteria (KKM ≥ 80), with a class average score of 74.6, indicating critically low writing proficiency. This study employed a Classroom Action Research (CAR) design following the Kemmis and McTaggart cyclical model, conducted over two action cycles in the even semester of the 2025/2026 academic year. Data were collected through written essay production tests and structured classroom observation sheets, then analyzed using quantitative descriptive and qualitative methods. The results showed a consistent and significant improvement across cycles: the class average score rose from 74.6 (pre-cycle) to 78.7 (Cycle I) and reached 82.9 (Cycle II), while the classical completion rate increased from 30.56% to 61.11% in Cycle I and further to 86.11% in Cycle II, successfully surpassing the 75% success indicator. These gains were driven by the shift from single static images to sequential interactive picture series in Cycle II, combined with individualized desk-by-desk teacher guidance. In conclusion, interactive picture media effectively scaffolds students' writing process by transforming abstract idea generation into concrete, structured visual experiences, thereby improving SPOK sentence construction, spelling accuracy, and writing self-confidence in elementary Indonesian language learning